EXPRESSION OF RELIGIOUS VOCABULARY AND SPIRITUAL VALUES THROUGH LANGUAGE - Sadriddinzoda Safiya Shaxobiddinovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the role of religious vocabulary as a linguistic tool for expressing spiritual values in the Uzbek language. It analyzes how religious terms reflect deep-rooted ethical and cultural meanings, both in traditional and contemporary contexts. The study also investigates how such vocabulary functions in communication, media, education, and public discourse, contributing to the preservation and transmission of moral and spiritual ideals. Attention is given to semantic shifts and pragmatic usage of religious lexicon in modern language environments.